Effects of Suprasegmental Phonological Alternations on Early Word Recognition: Evidence from Tone Sandhi - Wewalaarachchi, Thilanga D.; Singh, Leher (Frontiers in Psychology, 2016)
Early language acquisition is potentially complicated by the presence of many sources of variability in the speech signal. A frequent example of variability is phonological alternations, which can lead to context-driven changes in the realization of a word. The aim of the current study was to investigate effects of a highly frequent yet scarcely researched type of suprasegmental phonological alternation – tone Sandhi – on early spoken word recognition. The tone Sandhi rule investigated herein involves a tone change of the first syllable in a disyllabic unit. In accordance with third tone Sandhi, when two dipping tone syllables are juxtaposed in connected speech, the first syllable is dissimilated to a high rising tone. For example, ‘flour mill’ (unaltered pre-Sandhi form [fən(214) tʂʰɑŋ(214)]) undergoes tonal alternation resulting in the altered post-Sandhi form [fən(35) tʂʰɑŋ(214)]. In the current study, preschoolers’ sensitivity to the effects of tone Sandhi when processing familiar words was investigated via a preferential looking paradigm. Words varied in their phonological form: words that were labeled with a phonological alternation due to Sandhi (Post-Sandhi); words that were labeled with an unaltered form when tone Sandhi was licensed (Pre-Sandhi); non-Sandhi words correctly produced (Correct Pronunciation); and words labeled with a phonological alternation of tone not associated with Sandhi rules (Mispronunciation). Post-Sandhi forms and correct pronunciations were associated with visual referents with comparable strength, with only a subtle processing cost observed for post-Sandhi forms in the time course of lexical selection. Likewise, pre-Sandhi forms and true mispronunciations were rejected as labels for visual references with comparable strength, with only subtle differences observed in the time course of lexical selection. Findings are discussed in terms of their impact on prevailing theories of lexical representation.